Program Bimbingan dan Konseling Hipotetik untuk Meningkatkan Kepercayaan Diri Siswa Sekolah Menengah Pertama - Adiamila Lingga Diany; Setiawati; Rina Nurhudi Ramdhani (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2024)
Junior high school students are in their early adolescence, which is 12-15 years of age, where students need to fulfill their teenage development tasks. Self-confidence is one that teenagers must fulfill in fulfilling their developmental duties and can accept themselves and how to behave and socialize with the environment. This study has the purpose of describing the confidence of eighth graders in SMP Negeri 9 Bandung, describing the confidence of eighth-grade female and male students in SMP Negeri 9 Bandung, As well as the design of guidance and counseling programs that can be implemented in developing the confidence of eighth graders in SMP Negeri 9 Bandung. This study is a quantitative study using a descriptive method with a confidence variable. The sample in this study was 329 students with techniques in sampling using a nonprobability sampling approach or a saturated sampling technique in which the entire population was sampled. The results of the study were seen that the confidence of 8th graders of Bandung Junior High School 9 was in the moderate category, female and male students did not have a significant difference. Guidance and counseling programs were created based on the results of research conducted on confidence.